Effect of Portions and Particle Sizes on Proximate Properties of Oil Palm Fronds. Issue 1 (December 2020) - Sirrajudin, Mohamed Sharizal; Salam, Mohammed Abdus; Ahmad, Azlan bin; Rak, Aweng Eh; Mohamed, Mazlan
Abstract: The purpose of proximate analysis is basically to evaluate the fuel characteristics of raw materials. So, the aim of this study is to evaluate the effect of portions and particle sizes on proximate properties of oil palm fronds. The moisture analyser mx-50 machine was used in the identification of moisture content (MC) in the samples. Meanwhile, volatile matter (VM) was analyze based on BS EN 15148:2009 standard. Ash content (AC) was obtained using BS EN 14775:2009 standard. On the other hand, fix carbon (FC) was obtained through the summation of percentage in all three (3) different values of moisture content, ash content and volatile matter subtracted from 100%. The average percentage of MC of bottom, middle and top portion of oil palm fronds for smaller particle size (0.5mm) were 11.91±0.25%, 12.23±0.14%, 12.59±0.23% respectively. On the other hand, the average percentage of MC of the same portion of oil palm fronds for bigger particle size (1.5mm) were 10.67±0.41%, 11.25±0.12%, 11.53±0.23% respectively. Meanwhile, the average percentage of VM of the same portion of oil palm fronds for smaller particle size (0.5mm) were 81.02±0.28%, 80.68±0.33%, 80.15±0.19% respectively. The average percentage of VM of the same portion of oil palm fronds for bigger particle size (1.5mm) were 82.48±0.32%, 82.48±0.32%, 81.26±0.26% respectively. The average percentage of AC of the same portion of oil palm fronds for smaller particle size (0.5mm) were 2.48±0.15%, 2.63±0.16%, 2.85±0.70% respectively and for bigger particle size were 2.23±0.11%, 2.46±0.71%, 2.67±0.50% respectively. Last but not least the average percentage of FC of the same portion of oil palm fronds for smaller particle size were 4.59±0.26%, 4.46±0.60%, 4.41±0.11% respectively and for bigger particle size were 4.62±0.33%, 4.57±0.15%, 4.54±0.02% respectively. Based on the results of proximate analysis above, it can be concluded that, oil palm fronds has a potential to be utilized as solid fuel.